A cross sectional study to assess factors related to exclusive breast feeding practice among mothers of infants aged six months or less admitted in pediatric wards at tertiary care hospital - Singh, Niti V.; Singh, Vijaykumar; Chowdhury, Soujannya K. (International Journal Of Community Medicine And Public Health, 2021)
Background: Infant feeding practices have a major role in determining the nutritional status of a child. Despite several benefits of exclusive breastfeeding, the practice is not common in many developing nations, including India. So there is a need to assess factors associated with exclusive breast feeding by mothers. Methods: A cross sectional study using the quantitative method by the means of a well prepared questionnaire, carried out in the pediatric ward of a tertiary care hospital in Mumbai. Data was collected by face to face interview and filed in a pretested, semi-structured, questionnaire. Data entry was done in excel sheet and analysed with the help of epi-info and statistical package for the social sciences (SPSS) software and was presented in tabular and graphical form. Results: A total of 112 mothers with infants <6 months of age participated in the study with a response rate of 98%. Conclusions: Majority of mothers’ perception about exclusive breastfeeding was that they considered it insufficient for their infant’s health and nutrition, and hence also relied on other feeds.